Peningkatan Kemampuan Menulis Teks Eksplanasi Menggunakan Model Pedagogi Genre, Saintifik, Dan CLIL - Elis Maryanti; Haryadi Haryadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Improving students' ability in scientific explanation and mastery of learning materials is one of the main goals in education. This study aims to explain the increase in the ability to write explanatory texts and mastery of students' concepts through the implementation of genre, scientific, and CLIL (content and language integrated learning) pedagogical models for fifth grade elementary school students. The research design uses a quantitative experiment. There are 2 variables in this study, namely the dependent variable (explanatory text), independent variables (genre, scientific, and CLIL pedagogical models). The population in this study were fifth grade elementary school students for the 2021/2022 academic year in Sleman Regency, Yogyakarta. Data analysis technique using paired t-test and ANOVA test. The results of this study were that learning to write explanatory texts using genre, scientific, and CLIL pedagogical models experienced a significant increase in students' ability to write explanatory letters. The results of the analysis through the normality test, homogeneity and t test using the SPSS version 20.0 for windows. Based on the results of the study, it was found that the students' pre-test writing ability score was 48 and the post-test score was 68.8. Based on the results of the t-test of students' writing ability, it is known that p = 0.00 ˂ 0.05. Thus it can be interpreted that the ability to write explanatory texts of students has increased after being given learning with genre, scientific, and CLIL pedagogical models. Suggestions from this study are for teachers to use genre, scientific, and CLIL pedagogical models in learning to write explanatory texts. This is intended so that learning to write explanatory texts can achieve the learning objectives. Keywords: Explanation text, Pedagogi Genre Models, CLIL, Saintific, Writing Skills.